Epitope map of human immunodeficiency virus type 1 gp41 derived from 47 monoclonal antibodies produced by immunization with oligomeric envelope protein. - Earl, P L (1997)
The biologically relevant form of the human immunodeficiency virus type 1 (HIV-1) envelope (Env) glycoprotein is oligomeric, with the major points of contact between oligomeric partners located in the ectodomain of gp41. To identify and map conserved epitopes and regions in gp41 where structure is influenced by quaternary interactions, we used a panel of 38 conformation-dependent and 9 conformation-independent anti-gp41 monoclonal antibodies (MAbs) produced by immunization of mice with oligomeric Env protein. By cross-competition experiments using these MAbs and several others previously described, six distinct antigenic determinants were identified and mapped. Three of these determinants are conformational in nature and dependent in part on Env oligomeric structure. MAbs to two of these determinants were broadly cross-reactive with Env proteins derived from primary virus strains. The prevalence of antibodies in HIV-1-positive human sera to the antigenic determinants was determined by the ability of such sera to block binding of MAbs to Env protein. Strong blocking activity that correlated with cross-reactivity was found.